2014
DOI: 10.2169/internalmedicine.53.1720
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Aortic Stiffness and the Left Ventricular Function in Patients with Prediabetes

Abstract: Objective Several studies have shown that arterial stiffness and ventricular dysfunction are increased in individuals with type 2 diabetes. Aortic stiffness (AS) reflects the mechanical tension and elasticity of the aorta, and increased aortic stiffness is a risk factor for cardiovascular disease. The aim of this study was to evaluate the degree of aortic stiffness and its relationship with the left ventricular (LV) function in patients with prediabetes and healthy control subjects. Methods The study groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Myocardial hypertrophy, ischemia, and age are the most common causes of DD. Diastolic functions are impaired among patients with hypertension, diabetes, and coronary artery disease [20]. We found that patients with DD had more impaired aortic elasticity, higher CACS, more total plaque area, and higher EFV.…”
Section: Discussionmentioning
confidence: 94%
“…Myocardial hypertrophy, ischemia, and age are the most common causes of DD. Diastolic functions are impaired among patients with hypertension, diabetes, and coronary artery disease [20]. We found that patients with DD had more impaired aortic elasticity, higher CACS, more total plaque area, and higher EFV.…”
Section: Discussionmentioning
confidence: 94%
“…41,42 In this way, we detected a high-risk population who can benefit by a simple and close echocardiographic follow-up, to catch the signs of systolic and diastolic myocardial dysfunction at the beginning. 30,41 The study has some limitations. First, even if aortic tissue strain is a new application of TDI which has proved to be useful in studying the aortic elastic properties of patients with hypertension, diastolic dysfunction with elevated filling pressures, 43 type 1 diabetes mellitus, 44 coronarosclerosis, 45 subclinical hypothyroidism, 46 and previously preeclamptic women, 21 this methodology is not yet widespread and accepted.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in our study for the first time, we demonstrate the additive role of T2DM on hypertension in causing an arterial stiffness . In this way, we detected a high‐risk population who can benefit by a simple and close echocardiographic follow‐up, to catch the signs of systolic and diastolic myocardial dysfunction at the beginning …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, it reflects the cardiovascular burden of the relevant subject. In the studies dealing with arterial stiffness, pulse wave velocity (PWV) technique has been used extensively, but echocardiography has not been used effectively to measure arterial stiffness (10)(11)(12) . It is a very valuable tool in this aspect since it measures central arterial rather than peripheral arterial stiffness, which has better correlation with cardiovascular outcome (13) .…”
Section: Research Articlementioning
confidence: 99%